Impact of Work Environment, Workload, Stress, and Motivation on Employee Performance in MSMEs - Ina, Ina Maghfiroh; Efriyani Sumastuti; Bayu Kurniawan (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study examines the impact of work environment, workload, job stress, and work motivation on employee performance in the Micro, Small, and Medium Enterprises (MSMEs) sector in Demak Regency. A sample of 107 respondents was selected using purposive sampling, and data were collected via questionnaires. Multiple linear regression analysis, t-tests, and the coefficient of determination (R²) test were employed to analyze the data. The results indicate that both work environment and workload have a positive and significant impact on employee performance, while job stress shows no significant effect. Work motivation negatively influences employee performance, suggesting that excessive motivation without proper management can reduce productivity. These findings provide valuable insights for improving employee performance in the MSMEs sector by fostering a healthy work environment and optimizing workloads. The study recommends strategies such as employee training, improved communication, and non-material rewards to enhance motivation and performance. Keywords: Work Environment, Workload, Work Stress, and Motivation